The accuracy of a forecast targeting central bank - Nina Skrove Falch; Ragnar Nymoen (Kiel Institute for the World Economy (IfW), 2011)
This paper evaluates inflation forecasts made by Norges Bank which is recognized as a successful forecast targeting central bank. It is reasonable to expect that Norges Bank produces inflation forecasts that are on average better than other forecasts, both 'naïve' forecasts, and forecasts from econometric models outside the central bank. The authors find that the superiority of the Bank's forecast cannot be asserted, when compared with genuine ex-ante real time forecasts from an independent econometric model. The 1-step Monetary Policy Report forecasts are preferable to the 1-step forecasts from the outside model, but for the policy relevant horizons (4 to 9 quarters ahead), the forecasts from the outsider model are preferred with a wider margin. An explanation in terms of too high speed of adjustment to the inflation target is supported by the evidence. Norges Bank's forecasts are convincingly better than 'naïve' forecasts over the second half of our sample, but not over the whole sample, which includes a change in the mean of inflation.
Keywords: C32; C53; E37; E44; E47; E52; E58; E65; 330; inflation forecasts; monetary policy; forecast comparison; forecast targeting central bank; econometric models